2016
DOI: 10.12659/msm.898538
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia, Cognitive Function, and Mobility in an Outpatient Heart Failure Population

Abstract: BackgroundThe association of hyponatremia with cognitive impairment and mobility in heart failure (HF) patients is unknown. The purpose of this study was to determine if hyponatremia is associated with cognitive and mobility impairment as measured by simple, validated, and time-sensitive tests.Material/MethodsThis was a prospective study in patients with reduced and preserved ejection fraction (HFrEF, HFpEF) seen in outpatient HF clinics. Hyponatremia was defined as sodium level ≤136 mEq/L. Cognitive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
(38 reference statements)
2
22
0
Order By: Relevance
“…HF patients have elevated levels of coagulation markers such as D-dimer [10] . Hypercoagulability in HF could be derived from many causes, such as blood stasis, hemodynamic disorders [36] , [37] , [38] , impaired cardiac structure and/or function, dilatation of cardiac chambers, reduced myocardial contractility, low cardiac output, mobility limitation [39] , increased intra-cardiac and central venous pressure, inflammation activation [40] , neuro-hormonal activation, impaired endothelial function, and arrhythmias such as AF [5] , [7] , [38] , [40] , [41] , [42] . The hypercoagulability status predisposes the patients to embolic events, and anticoagulation therapy could be associated with better clinical outcomes [11] .…”
Section: Discussionmentioning
confidence: 99%
“…HF patients have elevated levels of coagulation markers such as D-dimer [10] . Hypercoagulability in HF could be derived from many causes, such as blood stasis, hemodynamic disorders [36] , [37] , [38] , impaired cardiac structure and/or function, dilatation of cardiac chambers, reduced myocardial contractility, low cardiac output, mobility limitation [39] , increased intra-cardiac and central venous pressure, inflammation activation [40] , neuro-hormonal activation, impaired endothelial function, and arrhythmias such as AF [5] , [7] , [38] , [40] , [41] , [42] . The hypercoagulability status predisposes the patients to embolic events, and anticoagulation therapy could be associated with better clinical outcomes [11] .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that peak VO 2 /HR is important in the pathophysiology of cognitive impairment compared with any other cognitive‐related potential factors (usual walking speed, TUG, aortic pulse wave velocity, and sarcopenia) among community‐dwelling older adults with preserved EF. Recently, a high prevalence of cognitive impairment was reported in patients with chronic HF (both HF with reduced and preserved EF). Interestingly, we found that peak VO 2 /HR is related to skeletal muscle mass index, which is an important factor in sarcopenia, and hypothesized that the decline of peak VO 2 /HR with decreased skeletal muscle mass in sarcopenia is a phenotype of HF with preserved EF .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chronic heart failure (HF) with both reduced and preserved ejection fraction (EF) has been associated with a high prevalence of cognitive impairment . Atrial fibrillation is a known risk factor for cognitive decline and dementia due to the attenuated ability to elevate cerebral perfusion during exercise because of the impaired ability to increase CO .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that many medical comorbidities play an important role in the pathogenesis of cognitive impairment in CHF patients, including hypertension [9], type 2 diabetes mellitus [10], atrial fibrillation [11], obesity [12], chronic renal dysfunction [13], anemia [14], hyponatremia [15], depression [16], and sleep apnea [17]. However, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%